Social implications of using online alternative media towards participatory democracy in Malaysia - Kamaruddin, Azlina; Ghazali, Rahmat; Muda, Mariah (AstonJournals, 2015)
Modern technology has resulted in rapid communication over unlimited space and it must be understood as a network of human and non-human actors bound together in seamless web. In this context, understanding the Internet should be in terms of the relationship between different actors to serve for participatory democracy.Now many types of horizontal dialogues are possible through email, chat rooms, discussion boards, usenets, real-time audio and video conferencing.Public feel disappointed since their opinions, needs, and consumptions were not well covered and reported through the mainstream media.Dissident voices become dominant group in order to voice out their views.This study explores the social implications of using online alternative media towards participatory democracy in Malaysia.The method employed for the collection of data is through phenomenological study where the data were collected using online asynchronous interview via emails. The researcher used thematic analysis. Nine themes emerged for the data analysis which falls under social implication.Participants need to fulfill eight criteria of being selected as interview participants.The findings showed that there is high level of awareness among the general public to participate through online alternative media.They have tendency to contribute for participatory democracy.This study suggests to other researchers who are interested in doing the same area of this study to conduct a hyperlink study; to explore other websites or other resources to enable to see the whole macro picture about the implications of online media towards participatory democracy